STRATEGI INDONESIA DALAM MENINGKATKAN PARIWISATA MANDALIKA SEBAGAI SALAH SATU DESTINASI 10 BALI BARU TAHUN 2019-2021 - Inayah Helmy (2023)
The research in this thesis aims to find out and understand how Indonesia's strategy is in increasing Mandalika Tourism as one of the 10 New Bali destinations. This thesis research also uses the concept of nation branding and national interests. This study uses the theory of public diplomacy to analyze the achievements of Indonesian public diplomacy in the tourism sector, several steps of public diplomacy include diplomacy through international sporting events, exhibitions and festivals, as well as foreign promotions in increasing Mandalika tourism as one of the 10 new Bali destinations. In the process of analysis, the author uses a qualitative case study method to provide descriptive answers based on the facts found. The author found that there was a decrease in the number of tourist visits in Indonesian territory, including Mandalika. However, Indonesia's achievements have received a positive reputation by the public.